Improving spectrum efficiency on cognitive radio spectrum sensing with enhanced diversity concept / Mohsen Akbari - Mohsen, Akbari (2016)

(untitled)
The frequency spectrum is a scarce resource for wireless communication. Due to the rapid advances in a wireless communication system, there has been an increasing demand for the new wireless services in both the used and unused Electromagnetic spectrum. However, this increasing demand faces a great barrier which is the limitation of radio resources. FCC researches proved that the main reason for the scarcity of spectrum is the underutilization of frequency spectrum by the licensed users either temporally or spatially. To overcome this problem scientists have used new model known as cognitive radio (CR) that is envisioned as a promising paradigm of exploiting intelligence for enhancing efficiency of underutilized spectrum bands. Frequently monitoring spectrum bands is the main feature of CR networks and the other characteristic is detection of occupancy and then opportunistically usage of spectrum holes with least possible interference with primary user (PU) caused of secondary users (SUs). Users in the CR network must determine which portions of the spectrum are available, Select the best available channel, coordinate access to this channel with other users and vacate the channel when a licensed user is detected. These capabilities can be realized through spectrum management functions that address four main challenges: spectrum sensing, spectrum decision, spectrum sharing, and spectrum mobility. To the benefit of readers a brief overview of cognitive radio and the current research challenges of spectrum management is presented and new algorithm is proposed to improve QoS in CR system especially in sensing and decision part. At the first step, this research proposes an analytical study on the optimality of common soft decision fusion (SDF) cooperative spectrum sensing (CSS) and decision based on the modified imperialistic competitive algorithm (ICA) at which low total probability of error (